Information and communication technology as a motivating factor in learning graphic disciplines (Pedagogy of Higher and Secondary Education, 2014)
Tsvirkun L. O. Information and communication technology as a motivating factor in learning graphic disciplines.The possibilities of information and communication technologies that increase the attention and enthusiasm for learning graphic disciplines due to the visibility and visualization, it is found that the performance of the tasks of modeling, engineering and graphic works and educational projects with the help of modern graphics software enhances motivation in graphic preparation.
Keywords: engineer; graphic disciplines; information and communication technolog; motivation; design and engineering expertise